Efecto de herbicidas pre-emergentes sobre la siembra directa de semillas pregerminadas de Gmelina arborea Roxb. y Gliricidia sepium (Jacq.) Kunth ex Walp. para el establecimiento de plantaciones dendroenergéticas - Hernández, Natalia (Editorial Tecnológica de Costa Rica, 2018)
This study addresses the need to find preemergence herbicides for the direct sowing of seeds of forest species dedicated to the establishment of energy plantations. Twelve different preemergence herbicides were evaluated on the direct sowing of two forest species with great potential for biomass production for bioenergy. One of the limiting aspects of the plantations energy is the high cost of establishment by concept of acquisition of plants, so we looked for the best options for direct sowing of pregerminated seeds of Gmelina arborea (Melina) and Gliricidia sepium (Black Madero), and offer an alternative in lowering costs. The experiment was carried out in a greenhouse (ITCR, Cartago), for 10 weeks, analyzing each species separately. A randomized complete block experimental design was used. The seeds were subjected to the best pre germination treatment and sown in pots, they were immediately atomized by the different pre-emergent herbicides following the protocol described in the methodology. At the end of the experiment it was determined that pre-emergent herbicides with the active ingredient of Linuron and Oxyfluorfen can be used in the direct sowing of Melina, as they did not cause damage to plant yields, in addition to obtaining most of the parameters with statistically superior results. In the case of black Madero the pre-emergent Linuron obtained the best results, concluding that it can be useful for use in direct sowing. The pre-emergent herbicide with the active ingredient of Pendimethalin obtained the lowest yield results in almost all the parameters analyzed; For both species it produced the total death of the weeds before week 7.